Auf dem Weg zu einer Green Economy Wie die sozialökologische Transformation gelingen kann - Behrendt, Siegfried; Clausen, Jens; Göll, Edgar, 1957-; Kahlenborn, Walter, 1964- (Neue Ökologie Ser., 2019)
Green economy is the future - this volume illuminates options, challenges and factors of success, providing perspectives for politics and the economy.